Efficacy of melatonin as protectant against oxidative stress and structural changes in liver tissue in pinealectomized rats - Sahna, E; Parlakpinar, H; Vardi, N; Cigremis, Y; Acet, A (Urban & Fischer Verlag, 2004)
Previous observations demonstrated that physiological levels of metatonin, the pineal secretory product, are important in protecting against oxidative stress-induced tissue damage. We investigated the effects of pinealectomy and administration of exogenous melatonin on liver tissue in rats. Pinealectomized (Px) and sham-operated (non-Px) rats were used. We evaluated structural changes, reduced glutathione (GSH) levels and matondialdehyde (MDA) levels. Rats were divided into three groups (10 rats in each group): control. (non-Px), Px+vehicle and Px+metatonin (4 mg/kg given daily intraperitoneally for 10 days). Liver GSH levels were significantly tower in Px rats than in the control group. Melatonin administration significantly increased GSH levels (p<0.05). Px caused a significant increase in MDA levels as compared with the control group and metatonin administration to Px rats significantly reduced MDA levels in the liver (p<0.05). Sinusoidal dilatation to a varying degree developed in all Px rats. Severity of mononuclear cell. infiltration and sinusoidal congestion were tower in Px+melatonin group than in the Px group. These findings suggest that a significant increase in oxidative and structural changes occur in rat livers after pinealectomy, which can be diminished by melatonin treatment. (C) 2004 Published by Elsevier GmbH.
Keywords: melatonin; pinealectomy; glutathione; malondialdehyde; liver